Clarifying values for attitudes changes; a tool for improving quality assistance to women in abortion situation - Gómez Ponce, Rodolfo (2015)
Workshops on clarifying values and transformation of attitudes (CVTA) are useful in eliminating some of the access barriers to quality services for women in situation of abortion, barriers that derive from erroneous information, women and health care providers’ stigmatization, negative attitudes, and obstructionist behavior. Access barriers to safe abortion and post abortion services that follow lawful directions in Latin America are well documented. CVTA is one of various strategies used to assure women accessing services to obtain care quality they deserve. CVTA’s conceptual framework is based on programmed behavior theory and includes some of its elements: values theory and the three main stages of the clarifying values process. In order to be able to participate efficaciously in the clarifying values process with respect to abortion, one should be able to acquire new information, go into existing or new information knowledge in depth, experimenting empathy for persons that look for or offer integral abortion care, know their current values in relation to abortion, examine alternative values, determine barriers to change and be open to changes. Continuous support to CVTA process is an adequate tool for improving care quality to women in abortion situation.